Localized Tetanus: Rare and Elusive - Chaudhary, Raina; Karki, Binod; Bhatta, Sabita; Pradhan, Manoj (Medical Journal of Shree Birendra Hospital, 2013)
Tetanus is acute and fatal infectious disease which is acquired due to contamination of wound with soil or animal feces containing spores of Clostridium tetani. In this case, 24 old male, serving personnel of Nepalese Army, developed localized tetanus, a rare form of tetanus nearly 3 weeks following crocodile bite in his left thigh. It was painful with involvement of only local flexor muscles at the site of injury. The aim is to incite awareness of the rare form of the Tetanus in adult which is often overlooked in clinical practice.Medical Journal of Shree Birendra Hospital; January-June 2013/vol.12/Issue1/47-49DOI: http://dx.doi.org/10.3126/mjsbh.v12i1.9095